PENDAMPINGAN PENGOLAHAN LIMBAH PELEPAH DAN DAUN PISANG MENJADI PRODUK SPRAY ANTI NYAMUK DI KABUPATEN BOJONEGORO - Muhammad Faizin (DEVELOPMENT: Journal of Community Engagement, 2025)
This study aims to assist the community of Megale Village, Kedungadem District, Bojonegoro Regency in optimizing local assets in the form of abundant banana frond and leaf waste, which has not been economically utilized. The method employed is Asset Based Community Development (ABCD) with the Appreciative Inquiry (AI) cycle, involving 32 participants from the Fatayat, Muslimat, and PKK groups. The waste transformation process was conducted using simple distillation technology to extract phytochemical compounds, namely saponins and tannins, into anti-mosquito spray and aromatherapy products. The results indicated a significant increase in participants' knowledge capacity, with the average score jumping from 48.4 in the pre-test to 85.9 in the post-test (a 77.5% increase). In conclusion, banana waste processing through the ABCD approach is not only effective as a self-reliant health preventive solution but also serves as a milestone for local wisdom-based creative economic independence in rural areas.